Desarrollo de un sistema integral para el diseño de elementos estructurales - Rojas-Chávez, Daniel (Instituto Tecnológico de Costa Rica, 2015)
This document will focus on providing the company AESA, a series of electronic tools, to optimize the design of various structural elements of different materials such as iron, concrete and wood. Spreadsheets were developed for the calculation of different processes of design, using the Excel program (2010 version), and in turn aid also some Visual Basic, to grant a greater versatility to the user in cases where necessary. The purpose of this project is to provide the company AESA with standard spreadsheets for some processes, and that workers use only a single type of spreadsheet for the calculation and design of some structural elements.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2015.
Keywords: Compresión; Madera; Concreto; Acero; Excel